Modeling opinion polarization: can we control public discourse? - Demirci, Ali; Peker-Dobie, Ayse; Harman, Sevgi (Frontiers in Physics, 2025)
IntroductionPublic opinion dynamics shape societal discourse, with engagement levels influencing the balance between polarization and depolarization.MethodsWe present a compartmental model inspired by epidemiology to analyze opinion dissemination under external interventions. The model categorizes individuals into susceptible, exposed, positive, negative, and mixed-emotion communicators, with a time-dependent step function u(t) modeling controlled engagement surges during a finite intervention period.ResultsOur analysis focuses specifically on the effects of temporary interventions rather than long-term system evolution. The results highlight engagement as a key control mechanism in shaping ideological stability.DiscussionReal-world interventions, such as government-imposed access restrictions, demonstrate how targeted engagement shifts influence public discourse. This study provides a mathematical framework for understanding how external interventions drive opinion evolution and offers insights into managing polarization in digital and social environments.